Berberine ameliorates diabetic nephropathy by inhibiting TLR4/NF-κB pathway - Zhu, Liping; Han, Jiakai; Yuan, Rongrong; Xue, Lei; Pang, Wuyan (Biological research, 2018)
Diabetic nephropathy (DN) is the leading cause of end-stage renal failure, contributing to severe morbidity and mortality in diabetic patients. Berberine (BBR) has been well characterized to exert renoprotective effects in DN progression. However, the action mechanism of BBR in DN remains to be fully understood. The DN rat model was generated by intraperitoneal injection of streptozotocin (STZ, 65 mg/kg body weight) while 30 mM high glucose (HG)-treated podocytes were used as an in vitro DN model. The fasting blood glucose level and ratio of kidney weight to body weight were measured after BBR treatment (50, 100, or 200 mg/kg) in STZ-induced DN rats. The renal injury parameters including 24-h urinary protein, blood urea nitrogen and serum creatinine were assessed. qRT-PCR was performed to detect the transcript amounts of inflammatory factors. The concentrations of inflammatory factors were evaluated by ELISA kits. Western blot analysis was conducted to measure the amounts of TLR4/NF-κB-related proteins. The apoptotic rate of podocytes was analyzed by flow cytometry using Annexin V/propidium iodide. Berberine reduced renal injury in STZ-induced DN rat model, as evidenced by the decrease in fasting blood glucose, ratio of kidney weight to body weight, 24-h urinary protein, serum creatinine, and blood urine nitrogen. BBR attenuated the systemic and renal cortex inflammatory response and inhibited TLR4/NF-κB pathway in STZ-induced DN rats and HG-induced podocytes. Also, HG-induced apoptosis of podocytes was lowered by BBR administration. Furthermore, blockade of TLR4/NF-κB pathway by resatorvid (TAK-242) or pyrrolidine dithiocarbamate aggravated the inhibitory effect of BBR on HG-induced inflammatory response and apoptosis in podocytes. Berberine ameliorated DN through relieving STZ-induced renal injury, inflammatory response, and podocyte HG-induced apoptosis via inactivating TLR4/NF-κB pathway.